EPISTIMOLOGI POLITIK EKONOMI ISLAM: KAJIAN DALAM PEREKONOMIAN NEGARA - Neni Hardiati; Chaerul Shaleh; Fauzan Ali Rasyid (ITB AAS INDONESIA Surakarta, 2022)
Correct understanding of the basic elements in Islamic political economy is a necessity for its development. This writing attempts to trace the conceptual understanding of the basic elements of science, including the views and epistemology of Islamic economic politics in a country. His position in constructing the methodology of Islamic political economy to become the main topic. So that there are differences in the aims of epistemology and the framework of the methodology of Islamic political economy with the West. The consequences of these differences lead to differences in science. At the practical level, this gives rise to differences in determining policies. Meanwhile, logic, coherence and consistency are important prerequisites for a scientific approach. Islamic economic politics must be studied through its own epistemological view. However, on the other hand, we cannot deny the role and position of political science and economics today in the process of developing Islamic political economy. The study of political-economic epistemology covers the role of the state in the economy, especially in terms of public policy. Keywords: Epistemology, Islamic Political Economy, State Economy